An empirically based path loss model for indoor wireless channels in laboratory building - Supachai Phaiboon (2018)
This paper present a statistical indoor path loss model derived from 1.8 GHz experimental data collected in laboratory building. There are two models which are considered, 1) Distance-dependent path loss model and 2) Floor attenuation factor (FAF) path loss model. These models have been developed based on the number of floors, concrete and mirror walls between the transmitter and the receiver, and provide simple prediction rules which relate signal strength to the log of distance. The standard deviation between measured and predicted path loss is 8.7 dB for the entire data set. Average floor attenuation factors (FAF), which describe the second path loss (in decible) caused by floors between transmitter and receiver are found for as many as three floors in the typical building.